Literature Review: Elements of Place Attachment in Supporting the Preservation of Traditional Houses - Ferdian Faudy Fikri; Prasetyo Wahyudie (Green Publisher Indonesia, 2025)
Traditional houses are significant cultural symbols embodying a community's identity, history, and values. However, their preservation is increasingly threatened by modernization, shifting societal values, and a preference for contemporary housing, risking the loss of important cultural heritage. This study aims to create a conceptual framework by reviewing literature on place attachment and its essential role in the preservation of traditional houses. Employing a systematic literature review method, this research analyzes empirical studies, primarily from Indonesia, that explore the relationship between people and their living environments. The approach involves identifying and synthesizing relevant research articles to trace the evolution of place attachment concepts. The review identifies that the preservation of traditional houses is driven by four key elements of place attachment: place identity (connection to history and culture), place affect (emotional attachment), place dependence (support for daily life and culture), and place social bonding (strengthening community ties). The findings highlight that effective preservation strategies must extend beyond physical restoration to reinforce the emotional and social bonds communities share with their traditional homes. This conceptual framework underscores the need for holistic approaches that integrate these attachment elements to ensure the continuity of cultural heritage.